A comparison of lexical richness in L2 written productions - Engku Ibrahim, Engku Haliza; Muhamad, Ainon Jariah; Esa, Zaleha (2019)
Indeed research has shown that vocabulary acquisition is one of the chal-lenges of a language learner; even more so for productive vocabulary. Thus this study intends to investigate the lexical richness of 2 groups of EFL learners. This was done through a content analysis of 139 essays of entry-level university students and 140 essays of third-year university students studying at an English medium university. Both these groups of students scored at least a band 6 or 550 in TOEFL. Specifically, the objective of this study is to find out if there are differences in the lexical richness of these two groups of essays in the type-token ratio. This study also intends to find out if there are differences between the two different groups of essays in the use of the 1,000, 2,000, word levels, the AWL as well as the use of the words not-in-the-list. The RANGE programme developed by Nation, Heat-ley & Coxhead (2002) was used to carry out the above procedure. Findings of the study showed that the two groups of essays show a statistically significant difference in the use of the 1,000, 2,000, word levels and the AWL by the two groups of learners. There was also a difference in the not-in-the-list category. This research has pedagogical implications for the teaching of vocabulary in the language classroom with a specific focus on the development of lexical richness in EFL learners’ written production.